Manifestation of Trauma: The Effect of Early Traumatic Experiences and Adult Attachment on Parental Reflective Functioning - San Cristobal, Pamela; Santelices, Maria P.; Miranda Fuenzalida, Daniel A. (Frontiers in Psychology, 2017)
Transitioning into parenthood can be prove difficult even in the best of circumstances, however different risk factors can provide the experience of parenthood with even greater difficulties. Parents with the experience of childhood trauma can experience various types of disruptions in the parent/child relationship, among these parental reflective functioning. This study aims to expand on the line of research concerned with the effects that trauma has once that child transitions into adulthood and into parenthood by looking at the role that the experience of trauma and adult attachment has in relation to parental reflective functioning. This study assessed mothers (N=125) by using the CTQ (childhood experience of trauma), ECR (adult attachment), and the PRFQ (parental RF). Our study found that in the presence of physical neglect, insecure attachment had a particularly deleterious effect on maternal reflective functioning. This relationship was not as strong in the absence of physical neglect.